1988
DOI: 10.1042/bj2560853
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional variations in skeletal-muscle and scallop muscle actins

Abstract: Structural and functional properties in two striated-muscle actins, one from a vertebrate, the other from an invertebrate (scallop), were compared in relation to a smooth-muscle actin isoform (aortic actin). In spite of differences in the variable N-terminal region, the two striated-muscle isoactins showed, in contrast with aortic actin, a large structural homology revealed by proteinase-susceptibility and interaction with the myosin head. Thus the myosin head may bind to the two striated-muscle actins in cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In all cases the Vmax for the actin-activated myosin ATPase was the same. Only in comparisons of actin and myosin from scallop and rabbit skeletal muscle was a difference in Vmax found: homologous systems gave higher Vmax values, but no difference in the affinity of each actin for either myosin [113]. Since such comparisons are often conducted in non-physiological conditions and any differences can often be eliminated by varying pH or ionic strength [111], it is unclear if any of these in vitro differences are relevant to the situation in vivo [111].…”
Section: Comparison Of Naturally Occurring Actins Conservation Of Actmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases the Vmax for the actin-activated myosin ATPase was the same. Only in comparisons of actin and myosin from scallop and rabbit skeletal muscle was a difference in Vmax found: homologous systems gave higher Vmax values, but no difference in the affinity of each actin for either myosin [113]. Since such comparisons are often conducted in non-physiological conditions and any differences can often be eliminated by varying pH or ionic strength [111], it is unclear if any of these in vitro differences are relevant to the situation in vivo [111].…”
Section: Comparison Of Naturally Occurring Actins Conservation Of Actmentioning
confidence: 99%
“…Since such comparisons are often conducted in non-physiological conditions and any differences can often be eliminated by varying pH or ionic strength [111], it is unclear if any of these in vitro differences are relevant to the situation in vivo [111]. Furthermore, proteins which interact with actin will have coevolved [86,113]. [114].…”
Section: Comparison Of Naturally Occurring Actins Conservation Of Actmentioning
confidence: 99%
“…These populations were known to map the following regions 1-7, 18-28, 40-113, 168-226 and 285-375 in the primary sequence of skeletal muscle actin. The production of the antigenic populations as well as the location of the related isotopes have been described elsewhere Roustan et al, 1986;M› et al, 1988;Boyer et al, 1987). Thus, we have shown that the chemical treatment supported by actin was able to condition the specificity of produced antibodies.…”
Section: Antigenic Properties Of Muscle Invertebrates Actinsmentioning
confidence: 87%
“…Concerning actins from invertebrates (Pecten maximus), amino-acid substitutions at residues 103, 358 and 365 [30] are located in motifs al and a2 and two of them (103 and 365) concern ATPdependent binding sites. We demonstrated [31] that these mutations were responsible for a decrease in the Vmax of actinactivated Mg-ATPase of skeletal myosin. A few induced mutations in Drosophila were obtained (G368E and E316K), resulting in normal muscle structure while reducing S1 rigor binding [32], and altering the kinetics of force generation [33].…”
Section: ~3 Precise Local Analysis Of Hydrophobic Motifs a And Bmentioning
confidence: 89%